Research on Knowledge, Attitudes, and Practices of Influenza Vaccination Among Healthcare Workers in Chongqing, China—Based on Structural Equation Model - Chen, Siyu; Jiang, Yueming; Tang, Xiaojun; Gan, Lin; Xiong, Yu; Chen, Tao; Peng, Bin (Frontiers in Public Health, 2022)
【Abstract】Background: Influenza is associated with a large number of disease burden, and it is generally recommended that all health care workers should get influenza vaccination. However, the vaccination rates among health care workers are still low. This study was to assess health workers’ knowledge, attitude and behavior (KAP) about the influenza vaccine, and by establishing a structural equation model to explore the influencing factors of medical personnel influenza vaccination in Chongqing, China. Methods: From September to November 2019, we conducted a cross-sectional survey in 4 sentinel hospitals and 4 non-sentinel hospitals in Chongqing, China. We calculated knowledge, attitude and behavior scores for each study participant and assessed the level of knowledge, attitude and behavior of the medical staff. Structural Equation Model (SEM) was used to evaluate the relationship between latent variables, and the path graph between knowledge, attitude and behavior was established. Results: A total of 1412 valid questionnaires were collected in this survey, including 4 sentinel hospitals (N=606,42.92%) and 4 non-sentinel hospitals (N=806,57.08%). Females (N=1102,78.05%) were more than males (N=310 21.95%), with an average age of 32.36±7.78 years old and under 30 years old (N=737,52.20%), nurses (741,52.48%) were the main subjects, followed by physicians (457,32.37%). The final SEM model was obtained after the model was modified and adjusted. Bootstrap analysis of path coefficients was carried out on the final model. Knowledge has a direct influence on behavior. The normalized path coefficient is 0.071(95%CI: 0.002-0.161), and the P value of hypothesis test result of path coefficient is 0.042. The direct influence of knowledge on attitude standardization was 0.175(95%CI: 0.095-0.281). The direct influence of attitude on practice standardization was 0.818(95%CI: 0.770-0.862). The indirect effect of knowledge on standardization of practice through attitude was 0.144(95%CI: 0.076-0.235).Conclusions: According to the SEM, there is a direct positive correlation between knowledge, attitude and practice of influenza vaccine. The indirect influence of knowledge on the standard of behavior through attitude is about twice as much as the direct influence on behavior, indicating that attitude plays a strong mediating role between knowledge and practice.